EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP SIKLUS PENJUALAN OLE SUITES HOTEL - Lela Fitriyani; Ade Budi Setiawan; Maria Magdalena Melani (Bajang Institute, 2024)
This study plans to evaluate the application of accounting information systems to the sales cycle at the Ole Suites Hotel. This research is a type of descriptive research with a qualitative approach, namely collecting and analyzing data obtained from companies/agencies which are then returned to obtain a clear description or picture of the problems discussed in this study, namely the analysis of accounting information systems for sales of room services in order to support control intern at the ole suites hotel. The data analysis used by the author uses the Romney & Steinbart accounting information system approach (2018:10), while the Data Analysis used by the author uses the COSO approach (2013). This study obtained the results that the Sales Accounting Information System at the Ole Suites Hotel was good, because it was in accordance with the sales accounting information system theory according to Romney and Steinbart, only that there were employees who did not keep records for certain transactions. Internal Control At the Ole Suites hotel is still not in accordance with COSO theory, namely there are still shortcomings in risk assessment, namely the company has used the system but for input there is still a manual so there is the possibility of wrong input. In addition, in Control Activities, the credit sales function should be separate from the reception function, but at Ole Suites Hotel it is carried out by the same person / function and for receiving orders from buyers it is authorized by the marketing function with an order letter form, but Ole Suites Hotel is already using the system.